THE INFLUENCE OF VARIATION MODEL OF BRASS CATALYTIC CONVERTER ON EXHAUST EMISSIONS AND ENGINE PERFORMANCE - Karyasa, Tungga Bhimadi; Syamsuri, Syamsuri (TURBO [Tulisan Riset Berbasis Online], 2024)
The increase in motorized vehicles has resulted in air pollution. The result of incomplete combustion causes disease and contributes to global warming. From the problem of incomplete combustion residues, the researcher studied reducing exhaust emissions using brass catalytic converters with Flat Perforated Plate Type, Folded Perforated Plate Type, and Rolled Brass Sheet models. This research method used a Revo Absolute motorcycle's idle engine speed of 2000 rpm. This test used a gas analyzer and a dyno test. This study found a significantreduction in carbon monoxide (CO) and hydrocarbon (HC) exhaust emission levels using the folded perforated plate type catalytic converter model compared to other models and standard exhaust. CO exhaust emission results produced 0.52% by Folded Perforated Plate, 1.6% by Rolled Brass Sheet, 1.7%by Perforated Plate Type, and 2.1% by standard exhaust. HC exhaust emissions resulted in 475 ppm on the Folded Perforated Plate, 755 ppm on the Rolled Brass Sheet, 1517 on the Perforated Plate Type, and 1857 on the standard exhaust. This research concluded that a brass catalytic converter could reduce exhaust emission levels. Engine performance power and torque were almost the same for all models.